Enhancing Drug Utilization Efficiency via Dish-Structured Triboelectric Nanogenerator - Chen, Qu; Deng, Wenjing; He, Jingjin; Cheng, Li; Ren, Pei-Gen; Xu, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the finding of severe side effects and low therapeutic efficacy along with cancer chemotherapy, there still remains a great challenge to benefit patients with curative effect. In this work, we designed a self-powered drug delivery system comprised with a current source derived from the disk TENG (D-TENG), and a pair of Au electrodes. Thus, cells seeded within the electrodes gap could be stimulated by the current followed with D-TENG`s working. Under the rotation frequency of about 7.4 Hz, the peak output current and voltage of the D-TENG reached to 3.7 μA and 135 V and achieved an average 2.8 μA of output current. Furthermore, the D-TENG also showed its good stability to output steady current in a long-term condition. When applying the electric stimulation by this self-powered drug delivery system, a chemotherapy drug, doxorubicin (DOX) had significantly uptake by cancer cells. Therefore, utilizing a novel TENG device as a part of chemotherapy would provide a new opportunity in future disease treatment.